Asymmetric Nash bargaining for cooperative operation of shared energy storage with multi-type users engagement - Xu, Mengyao; Yang, Yongbiao; Xu, Qingshan; Fang, Lele; Tang, Rongchuan; Ji, Hemu (Frontiers in Energy Research, 2024)
Shared energy storage offers substantial savings on construction costs and improves energy efficiency for users, yet its business model as an independent economic entity remains unclear. An optimal scheduling method for cooperative operation of shared energy storage among multiple user types is proposed in this paper, which relied on asymmetric Nash bargaining to define operational schedules and pricing strategies effectively. Initially, a cost-benefit model for shared energy storage operators, along with power generation users, demand-side consumers, and microgrid prosumers is developed. Then, a cooperative game framework is established using asymmetric Nash bargaining principles which decomposes the problem into two parts: minimizing social total cost through cooperative operation scheduling and determining service fee pricing for equitable benefit distribution. For benefit distribution, the bargaining power of users is adjusted based on their alliance contribution, ensuring revenue distribution is aligned with individual contributions and improving fairness in pricing. Subsequently, the adaptive penalty factor alternating direction multiplier method (ADMM) algorithm is employed for distributed equilibrium solving, enhancing the convergence speed and safeguarding user privacy. Finally, the economics and feasibility of the proposed cooperation framework for shared energy storage are validated through a numerical example.